Intermediate bronchial kinking after right upper lobectomy for lung cancer. (January 2021) - Arai, Hiromasa; Tajiri, Michihiko; Masuda, Haruhiko; Sekine, Akimasa; Okudela, Koji; Komatsu, Shigeru; Iwasawa, Tae; Masuda, Munetaka
Background: Bronchial kinking after lung lobectomy is likely, whereas that of the intermediate bronchus after right upper lobectomy is often not recognized. The aim of this study was to examine the clinical implications of this condition. Methods: One-hundred cases of right upper lobectomy for primary lung cancer were reviewed. The cases were divided into groups with intermediate (group A) and non-intermediate (group B) bronchial kinking, and the patient characteristics and postoperative outcomes were compared. The remaining lower lobe deformation was also evaluated using the angle formed by the intrathoracic tracheal line and posterior fissure on reconstructed sagittal computed tomography. Results: There were 23 cases in group A which had a higher rate of bronchial calcification, older age, and female sex, whereas and smoking and pulmonary emphysema were less frequent. Three cases in group A had respiratory symptoms such as wheezing and respiratory noise, while only one case of middle lobe atelectasis was found in group B. In multivariate analysis, upper mediastinal lymph node dissection was an independent factor for non-intermediate bronchial kinking. The lower lobe was significantly more expanded in group A than in group B. Conclusions: Intermediate bronchial kinking correlates with postoperative respiratory symptoms and was less likely after upper mediastinal lymph node dissection.